THE RISE OF CYBORG CULTURE OR THE BOMB WAS A CYBORG - Porush, David (Surfaces, 1994)
Pictured by the author as a cybernetic rather than an atomic age, the Cold War is shown to be structured by the quest for a cybernetic modelling of human intelligence capable to eliminate uncertainty. The rise of the cyborg figure in science fiction is brought into consideration as an illustration.